ESTABLISHING DERIVED TEXTUAL ACTIVITY SCHEDULES IN CHILDREN WITH AUTISM. (29th May 2013) - Sprinkle, Evelyn C.; Miguel, Caio F.
<x xml:space="preserve">Abstract</x> Children with autism are frequently taught to follow picture activity schedules to increase independence in task engagement and transitions. As textual behavior allows for greater independence and efficiency in responding, schedules should rapidly become textual in form. Previous research has shown the effectiveness of conditional discrimination training and superimposition and fading procedures in establishing textual control. The current study evaluated the effectiveness of these procedures in establishing derived textual control in activity schedules. Participants included two children with autism (ages 3 and 8 years). Following the demonstration of proficiency in picture activity schedules, participants were exposed to superimposition and fading and conditional discrimination training in an alternating treatments design. Pretest–posttest measures were used to evaluate emergent relations among stimuli. Conditional discrimination training was superior to stimulus fading for emergent relations. The participants showed no clear difference between the procedures related to derived textual control. Copyright © 2013 John Wiley & Sons, Ltd.